The Impact of Explicit Instruction on Teaching Vocabulary to Fourth-Grade Students - Masrul Masrul; Bayu Hendro Wicaksono (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2023)
This research aimed to discover the impact of explicit instruction on teaching vocabulary to students with vocabulary difficulties. This explicit instruction involves directly teaching vocabulary words, providing detailed definitions, and practicing using these words in the context of sentences. The participants were 95 fourth-grade students. Participants who scored under 40 on the vocabulary test were randomly assigned to the experimental or control classes. The experimental group receives explicit instruction, while the control group receives conventional teaching from a teacher in a whole group setting. The experiment was conducted twice a week during 20 learning sessions. A teacher taught The reference group the same vocabulary as the whole group. Based on the data analysis using a mixed-model (multi-level) Time Condition analysis, the results remarked the moderate effect of the intervention on students' vocabulary knowledge and reading comprehension. Besides, the experiment group could write better sentences using the vocabulary taught than the control group. Research implication was also discussed